IMPROVING THE ACCURACY OF VIBRATION MEASUREMENT RESULTS - Stakhova, Anzhelika; Kvasnikov, Volodymyr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
The current state of control of vibration measuring equipment is studied in the work, the analysis of technologies of control of vibrating measuring machine equipment is carried out. It is determined that during the control a sufficient requirement for the analysis of changes in the state over time is to conduct periodic vibration measurements in the same modes of operation of the object. Therefore, the urgent task is to increase the reliability and accuracy of measurement results. It can be enhanced by obtaining additional information. For this purpose, recommendations for optimizing the vibration control points of the mechanism are formed. To increase the accuracy of measurement results when controlling the equipment for vibration signals, the methods of mounting the measuring transducer in the equipment monitoring system are considered. It is shown that the method of mounting the measuring transducer can affect the results of vibration measurements.